CHARACTERISTICS OF Al-Fe SINTERS MADE BY THE POWDER METALLURGY ROUTE (Metallurgy and Foundry Engineering, 2019)
The Al/Fe material was prepared by the powder metallurgy route with an additional intermediate stage which was a centrifuge of powder mixture. The application of the centrifuge stage was applied to obtain circular phase distribution of Al-rich phases in a sintered material. Iron powder with a particle size under 100 μm and aluminum powder with a particle size of about 25 μm, were used as starting materials. To determine the effect of centrifuging time on the distribution of Fe-Al particles, scanning electron microscopy (SEM, EDS) and XRD techniques were used. Microstructure observations show the influence of the centrifuging time on the distribution of Fe particles. It was observed that a longer centrifuging time caused changes in the ratio concentration of elements and allowed the growth of the intermetallic phase at the interface between solid Al and Fe particles.